2011
DOI: 10.1523/jneurosci.4345-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Role of the Cadherin/Catenin Complex at the Schwann Cell–Axon Interface and in the Initiation of Myelination

Abstract: Myelination is dependent on complex reciprocal interactions between the Schwann cell (SC) and axon. Recent evidence suggests that the SC-axon interface represents a membrane specialization essential for myelination; however, the manner in which this polarized-apical domain is generated remains a mystery. The cell adhesion molecule N-cadherin is enriched at the SC-axon interface and colocalizes with the polarity protein Par-3. The asymmetric localization is induced on SC-SC and SC-axon contact. Knockdown of N-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 39 publications
5
55
0
Order By: Relevance
“…That the Smad3 −/− phenotype is the more severe might be attributable to complete versus partial ablation of Tgfβ/Activin Smad-dependent signaling. The compensation seen in both genotypes also follows a precedent in other models displaying deficits in oligodendrocyte development and/or myelination (Montag et al, 1994;Larsen et al, 2006;Lewallen et al, 2011), although recovery is not a universal outcome (Meyerheim et al, 2004;Nolan et al, 2005;Emery et al, 2009). Our findings are also compatible with data from previous studies in mutants for MAP kinase components (Schwammenthal et al, 2004;Fyffe-Maricich et al, 2011).…”
Section: Smad3 Activity In Olig2supporting
confidence: 91%
See 1 more Smart Citation
“…That the Smad3 −/− phenotype is the more severe might be attributable to complete versus partial ablation of Tgfβ/Activin Smad-dependent signaling. The compensation seen in both genotypes also follows a precedent in other models displaying deficits in oligodendrocyte development and/or myelination (Montag et al, 1994;Larsen et al, 2006;Lewallen et al, 2011), although recovery is not a universal outcome (Meyerheim et al, 2004;Nolan et al, 2005;Emery et al, 2009). Our findings are also compatible with data from previous studies in mutants for MAP kinase components (Schwammenthal et al, 2004;Fyffe-Maricich et al, 2011).…”
Section: Smad3 Activity In Olig2supporting
confidence: 91%
“…Multiple pathways contribute to the generation of myelinating cells, and a strong precedent exists for recovery of myelination in mutants showing deficits in progenitor development (Montag et al, 1994;Larsen et al, 2006;Lewallen et al, 2011). Postnatally in Inhbb −/− spinal cords, the fraction of apoptotic Olig2 + cells remained slightly but significantly increased, and the fraction of cycling Ki67 + Olig2 + cells was marginally (but significantly) raised (Fig.…”
Section: Co-treatment With Tgfβ1 Plus Actb Enhances Myelin Formation mentioning
confidence: 94%
“…S8), although we cannot exclude the possibility that spectrins function downstream of these molecules during myelination. Indeed, N-cadherin and β-catenin are involved in establishing Schwann cell polarity and the timely initiation of myelination (19), and α-catenin, a binding partner of β-catenin, directly interacts with the αII and βII spectrin complex (20). Taken together, these findings strongly support the conclusion that loss of the spectrinbased cytoskeleton in Schwann cells impairs multiple mechanisms that contribute to proper PNS myelination.…”
Section: The Spectrin Cytoskeleton Is Polarized In Premyelinating Schsupporting
confidence: 58%
“…An intricate signalling network that involves between neurons and SCs controls nerve regeneration via signalling molecules such as neurotrophic factors and adhesion molecules [1,2]. Some studies have demonstrated the important role of the Ca 2+ -dependent glycoprotein neural cadherin (Ncadherin) in the growth and guidance of axons, as well as in cell adhesion (SC-SC and SC-axon contacts) and myelination [3][4][5][6][7][8][9]. These interactions are essential for SCs to form the bands of Bungner that bridge the injury site to provide an adhesive substrate for regrowing axons [1].…”
Section: Introductionmentioning
confidence: 99%